and Fig. 4.7.
For Fig. 4.6
(i) y = x
(ii) x + y = 0
(iii) y = 2x
(iv) 2 + 3y = 7%
For Fig. 4.7
(i) y = x + 2
(ii) y = x - 2
(ii) y = -x + 2
(iv) x + 2y = 6
4
TE
Y
(-1,3) 3
2 (0,2)
(
20)
1
1
(-1.1)
(0,0)
> X
X'
X't
-2
1 2 3
-2-1
1 2 3
1,-1)
-2
-3
Y
y
Fig. 4.6
Fig. 4.7
Answers
Answered by
1
Answer:
and Fig. 4.7. For Fig. 4.6 (i) y = x (ii) x + y = 0 (iii) y = 2x (iv) 2 + 3y = 7% For Fig. 4.7 (i) y = x + 2 ... - did not match any documents.
Suggestions:
Make sure that all words are spelled correctly.
Try different keywords.
Try more general keywords.
Try fewer keywords.
Similar questions